2016
DOI: 10.1080/02791072.2016.1179377
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Supportive Other Intervention for Opiate-Dependent Patients Entering Inpatient Detoxification

Abstract: Involvement of supportive others (SOs; defined as patient’s most important person) in substance treatment is widely accepted as a valuable addition to substance use treatment, but is not routinely implemented during inpatient detoxification for opioid use disorders. The current study explores the feasibility of a brief SO intervention for individuals detoxing from opioids. Data regarding ability to identify an SO, the nature of the SO relationship, and willingness to invite an SO to help with long-term abstine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(36 reference statements)
1
1
0
Order By: Relevance
“…Combined with the feedback from clinicians who implemented B-FIT, and the results of previous research (e.g., O'Farrell et al, 2008;Schonbrun et al, 2016) the results of the present study suggest a strong interest among clinicians, family members, and patients in involving families in brief AUD or SUD treatment, but the "formula" to do so still needs refinement and development. Several future refinements might enhance the generalizability of these interventions.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Combined with the feedback from clinicians who implemented B-FIT, and the results of previous research (e.g., O'Farrell et al, 2008;Schonbrun et al, 2016) the results of the present study suggest a strong interest among clinicians, family members, and patients in involving families in brief AUD or SUD treatment, but the "formula" to do so still needs refinement and development. Several future refinements might enhance the generalizability of these interventions.…”
Section: Discussionsupporting
confidence: 68%
“…Previous research on family engagement in inpatient settings has suggested that patients undergoing detoxification for opioid dependence (Schonbrun et al, 2016) and families of patients in AUD treatment (McCrady, Wilson et al, 2019) express enthusiasm for family involvement. However, one previous pilot study to engage families of patients undergoing detoxification from alcohol (O’Farrell et al, 2008) faced similar challenges in engaging families in the intervention—among 897 patients admitted to the detoxification program during the study, less than 25% (201) lived with a family member.…”
Section: Discussionmentioning
confidence: 99%